Ketamine for rapid reduction of suicidal ideation: a randomized controlled trial. Issue 16 (12th August 2015) - Murrough, J. W.; Soleimani, L.; DeWilde, K. E.; Collins, K. A.; Lapidus, K. A.; Iacoviello, B. M.; Lener, M.; Kautz, M.; Kim, J.; Stern, J. B.; Price, R. B.; Perez, A. M.; et al.
Abstract : Background: Suicide is a devastating public health problem and very few biological treatments have been found to be effective for quickly reducing the intensity of suicidal ideation (SI). We have previously shown that a single dose of ketamine, a glutamate N -methyl-d -aspartate (NMDA) receptor antagonist, is associated with a rapid reduction in depressive symptom severity and SI in patients with treatment-resistant depression. Method: We conducted a randomized, controlled trial of ketamine in patients with mood and anxiety spectrum disorders who presented with clinically significant SI ( n = 24). Patients received a single infusion of ketamine or midazolam (as an active placebo) in addition to standard of care. SI measured using the Beck Scale for Suicidal Ideation (BSI) 24 h post-treatment represented the primary outcome. Secondary outcomes included the Montgomery–Asberg Depression Rating Scale – Suicidal Ideation (MADRS-SI) score at 24 h and additional measures beyond the 24-h time-point. Results: The intervention was well tolerated and no dropouts occurred during the primary 7-day assessment period. BSI score was not different between the treatment groups at 24 h ( p = 0.32); however, a significant difference emerged at 48 h ( p = 0.047). MADRS-SI score was lower in the ketamine group compared to midazolam group at 24 h ( p = 0.05). The treatment effect was no longer significant at the end of the 7-day assessment period. Conclusions: The current findings provide initial support for the safety and tolerability of ketamine as an intervention for SI in patients who are at elevated risk for suicidal behavior. Larger, well-powered studies are warranted.